Potential for enhancing external beam radiotherapy for lung cancer using high-Z nanoparticles administered via inhalation. (26th August 2015) - Hao, Yao; Altundal, Yucel; Moreau, Michele; Sajo, Erno; Kumar, Rajiv; Ngwa, Wilfred
Abstract: Nanoparticle-aided radiation therapy is emerging as a promising modality to enhance radiotherapy via the radiosensitizing action of high atomic number (Z) nanoparticles. However, the delivery of sufficiently potent concentrations of such nanoparticles to the tumor remain a challenge. This study investigates the dose enhancement to lung tumors due to high-Z nanoparticles (NPs) administered via inhalation during external beam radiotherapy. Here NPs investigated include: cisplatin nanoparticles (CNPs), carboplatin nanoparticles (CBNPs), and gold nanoparticles (GNPs). Using Monte Carlo–generated megavoltage energy spectra, a previously employed analytic method was used to estimate dose enhancement to lung tumors due to radiation-induced photoelectrons from the NPs administered via inhalation route (IR) in comparison to intravenous (IV) administration. Previous studies have indicated about 5% of FDA-approved cisplatin concentrations reach the lung via IV. Meanwhile recent experimental studies indicate that 3.5–14.6 times higher concentrations of NPs can reach the lung by IR compared to IV. Taking these into account, the dose enhancement factor (DEF) defined as the ratio of the radiotherapy dose with and without nanoparticles was calculated for a range of NPs concentrations and tumor sizes. The DEF for IR was then compared with that for IV. For IR with 3.5 times higher concentrations than IV, and 2 cm diameter tumor, clinically significant DEF values of up to 1.19, 1.26, and 1.51 were obtained for CNPs, CBNPs and GNPs. In comparison values of 1.06, 1.08, and 1.15 were obtained via IV administration. For IR with 14.6 times higher concentrations, even higher DEF values were obtained e.g. 1.81 for CNPs. Results also showed that the DEF increased with increasing field size or decreasing tumor volume, as expected. The results of this work indicate that IR administration of targeted high-Z CNPs/CBNPs/GNPs could enable clinically significant DEF to lung tumors compared to IV administration during external beam radiotherapy. For FDA approved concentrations of CNPs or CBNPs considered, this could allow for additional dose enhancement to tumors via photoelectric mechanism during concomitant chemoradiotherapy.